BENTUK, FUNGSI DAN MAKNA MENHIR DI NAGARI MAHAT (Kajian Etnoarkeologi) - Hidayat, Romi (BALAI ARKEOLOGI PAPUA, 2011)
Nagari Mahat, located in Lima Puluh Kota Regency, West Sumatera, is a nagari which is rich for its stones. Those stones then become the materials to make the upright monumental stone (menhir) by the local artists. This research then focuses on the typology, function and the meaning of menhir for the community. There are approximately 800 menhirs in Nagari Mahat which are varied in shape, size and design. The data of the research is mainly from menhir in Koto Tinggi Site, Padang Ilalang Site, and Koto Gadang Site. Other than menhir, this research also collects the data about the behaviour of the local community in relation to the menhir they make.The typology of menhir that is classified based on the shape, design, and the technology is 367 menhirs, and from the artifact analysis found that there are 6 types of menhir. Overall the menhir has a distinct shape, there are the hilt of machete and sword, with tendril, double tendril and triangle shaped ornamental patterns. Menhir in Mahat is used as a burial, medium to worship the ancestors, land border, and the central for ceremonial activities. The meaning of its shape and design is symbolic to the one who is buried.